Effect of syncytiotrophoblast microvillous membrane treatment on gene expression in human umbilical vein endothelial cells. - Hoegh, A; Tannetta, D; Sargent, I; Borup, R; Nielsen, F; Redman, C; Sørensen, S; Hviid, T (2006)
OBJECTIVE: Syncytiotrophoblast membrane fragments (STBM) exist in the peripheral circulation in pregnant women and it has been shown that the level of circulating STBM is significantly increased with pre-eclampsia compared with uncomplicated pregnancies. STBM could be one of the factors which directly causes the endothelial cell dysfunction of pre-eclampsia. This study investigates the effect of STBM on endothelial cell gene expression. DESIGN: Human umbilical vein endothelial cells were cultured in the presence and absence of STBM. At specified time points, total RNA was purified from the cultures and analysed on microarrays. SETTING: A laboratory investigation using placentas obtained from a hospital delivery ward. SAMPLE: Placentas from nine healthy women were obtained. STBM vesicles were isolated from the placentas and umbilical vein endothelial cell cultures were established from the umbilical cords. METHODS: Gene expression was screened by Affymetrix GeneChips and confirmed with real-time polymerase chain reaction or enzyme-linked immunosorbent assay. MAIN OUTCOME MEASURES: Fold changes in gene expression levels between treated and control cultures were calculated from the microarray results. RESULTS: Overall, the results do not show any great changes in gene expression in endothelial cells after STBM treatment (28 genes changed two-fold or more out of approximately 10,000 genes examined by microarray). In general, the changes observed are consistent with inhibition of proliferation of endothelial cells by exposure to STBM. The unfolded protein response in particular may be involved. CONCLUSIONS: STBM may influence endothelial cell function during pregnancy but STBM alone cannot account for the entire range of endothelial dysfunctions observed in pre-eclampsia.